Inhibition of the Ras/Raf interaction and repression of renal cancer xenografts in vivo by an enantiomeric iridium(iii) metal-based compound. Issue 7 (15th June 2017) - Liu, Li-Juan; Wang, Wanhe; Huang, Shi-Ying; Hong, Yanjun; Li, Guodong; Lin, Sheng; Tian, Jinglin; Cai, Zongwei; Wang, Hui-Min David; Ma, Dik-Lung; Leung, Chung-Hang
Abstract : This study reports the first use of an iridium(iii ) compound and its enantiomer to inhibit the H-Ras/Raf-I PPI in vitro and repress renal cancer xenografts in vivo . Abstract : Targeting protein–protein interactions (PPIs) offers tantalizing opportunities for therapeutic intervention for the treatment of human diseases. Modulating PPI interfaces with organic small molecules has been found to be exceptionally challenging, and few candidates have been successfully developed into clinical drugs. Meanwhile, the striking array of distinctive properties exhibited by metal compounds renders them attractive scaffolds for the development of bioactive leads. Here, we report the identification of iridium(iii ) compounds as inhibitors of the H-Ras/Raf-1 PPI. The lead iridium(iii ) compound1 exhibited potent inhibitory activity against the H-Ras/Raf-1 interaction and its signaling pathway in vitro and in vivo, and also directly engaged both H-Ras and Raf-1-RBD in cell lysates. Moreover, 1 repressed tumor growth in a mouse renal xenograft tumor model. Intriguingly, the Δ -enantiomer of1 showed superior potency in the biological assays compared to Λ -1 or racemic1 . These compounds could potentially be used as starting scaffolds for the development of more potent Ras/Raf PPI inhibitors for the treatment of kidney cancer or other proliferative diseases.